Mechanical Distension Induces Serotonin Release from Intestine as Revealed by Stretchable Electrochemical Sensing. (23rd January 2020) - Liu, Yan‐Ling; Chen, Yan; Fan, Wen‐Ting; Cao, Pan; Yan, Jing; Zhao, Xing‐Zhong; Dong, Wei‐Guo; Huang, Wei‐Hua
Abstract: The role of endogenous serotonin (5‐HT) in gastrointestinal motility is still highly controversial. Although electrochemical techniques allow for direct and real‐time recording of biomolecules, the dynamic monitoring of 5‐HT release from elastic and tubular intestine during motor reflexes remains a great challenge because of the specific peristalsis patterns and inevitable passivation of the sensing interface. A stretchable sensor with antifouling and decontamination properties was assembled from gold nanotubes, titanium dioxide nanoparticles, and carbon nanotubes. The sandwich‐like structure endowed the sensor with satisfying mechanical stability and electrochemical performance, high resistance against physical adsorption, and superior efficiency in the photodegradation of biofouling molecules. Insertion of the sensor into the lumen of rat ileum (the last section of the small intestine) successfully mimics intestinal peristalsis, and simultaneous real‐time monitoring of distension‐evoked 5‐HT release was possible for the first time. Our results unambiguously reveal that mechanical distension of the intestine induces endogenous 5‐HT overflow, and 5‐HT level is closely associated with the physiological or pathological states of the intestine. Abstract : Die Rolle von endogenem Serotonin in verschiedenen Magen‐Darm‐Motilitätsmustern ist hoch kontrovers. Ein dehnbarer Sensor mit hoher Empfindlichkeit und anwuchsverhindernden sowie Dekontaminierungs‐Eigenschaften wird vorgestellt. Der Sensor wurde in das Lumen eines Darm‐Modells eingeführt und ermöglichte die Echtzeitüberwachung der durch Dehnung verursachten Abgabe von Serotonin.